Emergence of a New Population of Rathayibacter toxicus: An Ecologically Complex, Geographically Isolated Bacterium - Arif, Mohammad; Busot, Grethel Y.; Mann, R.; Rodoni, B.; Liu, Sanzhen; Stack, James (My University, 2016)
Rathayibacter toxicus is a gram-positive bacterium that infects the floral parts of several Poaceae species in Australia. Bacterial ooze is often produced on the surface of infected plants and bacterial galls are produced in place of seed. R. toxicus is a regulated plant pathogen in the U.S. yet reliable detection and diagnostic tools are lacking. To better understand this geographically-isolated plant pathogen, genetic variation as a function of geographic location, host species, and date of isolation was determined for isolates collected over a forty-year period. Discriminant analyses of recently collected and archived isolates using Multi-Locus Sequence Typing (MLST) and Inter-Simple Sequence Repeats (ISSR) identified three populations of R. toxicus; RT-I and RT-II from South Australia and RT-III from Western Australia. Population RT-I, detected in 2013 and 2014 from the Yorke Peninsula in South Australia, is a newly emerged population of R. toxicus not previously reported. Commonly used housekeeping genes failed to discriminate among the R. toxicus isolates. However, strategically selected and genome-dispersed MLST genes representing an array of cellular functions from chromosome replication, antibiotic resistance and biosynthetic pathways to bacterial acquired immunity were discriminative. Genetic variation among isolates within the RT-I population was less than the within-population variation for the previously reported RT-II and RT-III populations. The lower relative genetic variation within the RT-I population and its absence from sampling over the past 40 years suggest its recent emergence. RT-I was the dominant population on the Yorke Peninsula during the 2013-2014 sampling period perhaps indicating a competitive advantage over the previously detected RT-II population. The potential for introduction of this bacterial plant pathogen into new geographic areas provide a rationale for understanding the ecological and evolutionary trajectories of R. toxicus.
Citation: Arif, M., Busot, G. Y., Mann, R., Rodoni, B., Liu, S. Z., & Stack, J. P. (2016). Emergence of a New Population of Rathayibacter toxicus: An Ecologically Complex, Geographically Isolated Bacterium. Plos One, 11(5), 20. https://doi.org/10.1371/journal.pone.0156182
Keywords: Annual Ryegrass Toxicity; Clavibacter-Toxicus; Mitochondrial-Dna; Causative Agents; Genetic-Analysis; Lolium-Rigidum